Macroeconomic factor influence on agricultural program sustainability in Kaduna state, Nigeria - Hatzenbuehler, Patrick L.; Mavrotas, George (International Food Policy Research Institute, 2017)
In this study, we measure the degree to which a change in key macroeconomic variables, such as the global oil price, influences the ability for state Ministries of Agriculture to sustain agricultural program funding. To highlight the issue of dependence of state governments on the federal allocation, and the state Ministry of Agriculture on donor funds, a two-period simulation model was developed to represent the economy of Kaduna, a Nigerian state with a relatively large geographic scope and population. The simulation model results show that changes in the global oil price and levels of donor funds can have pronounced effects on state government and Ministry of Agriculture budgets. This implies that improved coordination between the FMARD and state Ministries of Agriculture and institutional mechanisms that can provide funding relief for state Ministries of Agriculture during poor fiscal conditions periods would help sustain agricultural programs over time.